IMPLEMENTASI NILAI – NILAI PANCASILA DALAM MENGHINDARI ALIRAN SESAT DI KEHIDUPAN BERAGAMA MASYARAKAT INDONESIA - Hafni Fauziyyah; Dinie Anggraeni Dewi (Universitas Muhammadiyah Enrekang, 2021)
This article has the purpose of exegeting and examining yaang's issues in society connected with the teachings of a cult connected with the implementation of niali - pancasila value. The scientific literature employs a qualitative approach study method. The discussion discussed a case of the alleged cult on banten as